MATEMATIKA SEBAGAI FONDASI KRITIS DALAM MENAKLUKKAN TANTANGAN SOAL FISIKA - Kamil, Firmanilah (Tadris IPA Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2023)
In education, there is a close relationship between math skills and understanding of physics concepts. These two subjects are considered the main foundation in science and technology. However, mastering these two areas simultaneously can be challenging for students in higher education. This article investigates the impact of math ability on college students' understanding and performance in solving physics problems. The purpose of this study is to measure the correlation value between mathematical ability and success in solving physics problems and analyze the relationship between students' mathematical abilities in solving physics problems. The study involved 60 students of D-III program in a polytechnic in basic physics course. The results showed a significant correlation between math ability and academic achievement in physics. Students with strong math skills tended to do better in physics. Analysis of students' responses to the math and physics tests indicated that students who were competent in math also performed well in physics, while students who were incompetent in math also faced difficulties in physics. Students who were unable to decipher answers in both subjects indicated the need for a better understanding in the fundamentals of mathematics to improve performance in physics.